Performance study of a phase change material Trombe wall system in summer in hot and humid area of China. (May 2022) - Li, Chao; Yang, Xun; Peng, Kewen
Abstract: In order to reduce the impact of daytime climate fluctuation on the performance of the Trombe wall system (TWS) and enhance its ventilation and cooling effect in summer, an improved phase change material (PCM) TWS was constructed in this study. In this paper, the thermal performance of the PCM TWS was evaluated by comparative experiments in hot and humid area of China in summer. The findings demonstrated that the PCM TWS provided more effective heat insulation than the common envelope and the typical TWS. During the day the PCM cold storage plate released the cooling capacity with a peak heat flow rate of - 25.1w/m 2 and it accumulated cold energy with a peak heat flow rate of 20.1w/m 2 during the night. The PCM TWS achieves better induced ventilation than the typical TWS, corresponding to a maximum room ventilation rate of 140m 3 /h (31h −1 ) and a minimum value of 29m 3 /h (6 h −1 ). The PCM TWS can significantly lower the indoor air temperature to a maximum of 2.1 °C compared to the typical TWS and 5 °C compared to the ordinary envelope.